CRISPR‐Cas9 Genome Editing in the Moss Physcomitrium (Formerly Physcomitrella) patens. Issue 4 (6th April 2023) - Wu, Shu‐Zon; Ryken, Samantha E.; Bezanilla, Magdalena
Abstract: Until recently, precise genome editing has been limited to a few organisms. The ability of Cas9 to generate double stranded DNA breaks at specific genomic sites has greatly expanded molecular toolkits in many organisms and cell types. Before CRISPR‐Cas9 mediated genome editing, P. patens was unique among plants in its ability to integrate DNA via homologous recombination. However, selection for homologous recombination events was required to obtain edited plants, limiting the types of editing that were possible. Now with CRISPR‐Cas9, molecular manipulations in P. patens have greatly expanded. This protocol describes a method to generate a variety of different genome edits. The protocol describes a streamlined method to generate the Cas9/sgRNA expression constructs, design homology templates, transform, and quickly genotype plants. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Constructing the Cas9/sgRNA transient expression vector Alternate Protocol 1 : Shortcut to generating single and pooled Cas9/sgRNA expression vectors Basic Protocol 2 : Designing the oligonucleotide‐based homology‐directed repair (HDR) template Alternate Protocol 2 : Designing the plasmid‐based HDR template Basic Protocol 3 : Inducing genome editing by transforming CRISPR vector into P. patens protoplasts Basic Protocol 4 : Identifying edited plants.